2018
DOI: 10.1021/jacs.8b08893
|View full text |Cite
|
Sign up to set email alerts
|

Principles Governing Catalytic Activity of Self-Assembled Short Peptides

Abstract: Molecular self-assembly provides a chemical strategy for the synthesis of nanostructures by using the principles of nature, and peptides serve as the promising building blocks to construct adaptable molecular architectures. Recently, a series of heptapeptides with alternative hydrophobic and hydrophilic residues were reported to form amyloid-like structures, which are capable of catalyzing acyl ester hydrolysis with remarkable efficiency. However, information remains elusive about the atomic structures of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 51 publications
3
38
0
Order By: Relevance
“…While its catalytic efficiency of 6.3±0.9 M −1 s −1 was lower than that of the unconstrained peptide assembly, it was nearly double the value of the corresponding β‐hairpin, oQQ, suggesting that additional stabilization provided by the macrocyclic structure can help overcome the inefficiencies of the linker. The macrocycle that forces parallel arrangements of the two strands, mQQ p , shows a value that is the same within the error of the measurement to that of mQQ a , consistent with the notion that while both antiparallel and parallel arrangements of the stands are productive, [5b] the relative positioning of the residues is critical for the activity as an antiparallel arrangement of the strands in peptide mQQ a* shows very little activity (Scheme 2, Table 2). These results are quite remarkable considering the difference in morphology between mQQ a and mQQ p , with the parallel macrocycles forming far more ordered and diffuse fibril networks upon self‐assembly (Figure 3).…”
Section: Resultssupporting
confidence: 74%
“…While its catalytic efficiency of 6.3±0.9 M −1 s −1 was lower than that of the unconstrained peptide assembly, it was nearly double the value of the corresponding β‐hairpin, oQQ, suggesting that additional stabilization provided by the macrocyclic structure can help overcome the inefficiencies of the linker. The macrocycle that forces parallel arrangements of the two strands, mQQ p , shows a value that is the same within the error of the measurement to that of mQQ a , consistent with the notion that while both antiparallel and parallel arrangements of the stands are productive, [5b] the relative positioning of the residues is critical for the activity as an antiparallel arrangement of the strands in peptide mQQ a* shows very little activity (Scheme 2, Table 2). These results are quite remarkable considering the difference in morphology between mQQ a and mQQ p , with the parallel macrocycles forming far more ordered and diffuse fibril networks upon self‐assembly (Figure 3).…”
Section: Resultssupporting
confidence: 74%
“…These structural studies revealed that the high-activity Ac-IHIHIQI-NH 2 peptide and its analogue, with Q6Y substitution which shows even higher activity, adopt a twisted parallel β-sheet structure while the lower activity peptide Ac-IHIHIRI-NH 2 forms a planar antiparallel β-sheet assembly. 155 In another study, fiber XRD was used to probe the fibril structure of the Ac-IHIHIYI-NH 2 peptide and related derivatives (in the presence and absence of Zn 2+ ), for which the Zn 2+ -dependent pNPA hydrolysis was also assayed. 105 Riek and co-workers examined the catalytic activity of a series of related designed amyloid peptides with alternating charged/uncharged residues with general sequence Ac-YV X 1 V X 2 V X 3 V-CONH 2 with X 1 , X 2 , X 3 = A, D, H or S (as well as Ac-IHIHIQI-NH 2 , for comparison), the catalytic activity for the most active example being shown in Table 1 .…”
Section: Catalysts Based On β-Sheet Structuresmentioning
confidence: 99%
“…In a previous study we also found that among these three peptides, that were tested at concentrations 50, 100 250 and 400 μM, for adsorption of the organophosphate paraoxon, ESH performed best at the fairly low concentration of 100 μM 37 . It is interesting to note that the internal dynamics of fibrils was also pointed out by others to be a pivotal factor in catalytic activity 52 .…”
Section: Discussionmentioning
confidence: 75%